Analisis Konteks Wacana dalam Buku Kumpulan Cerita Rakyat Daerah Se-Provinsi Riau - Tania, Evi; Hermaliza, Hermaliza (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
In fact every story is built by elements of the context of discourse. One of them is folklore, without context there will be no story, because it is the context of discourse that builds it. in the book collection of folklore of the region in Riau province the author found the existence of context in the form of background, participants, results, mandates, ways, means, norms and types in each story so as to make the story interesting to read. The problem in this research is how is the context of the discourse contained in the book collection of folklore in Riau Province? This study aims to describe, analyze, interpret and conclude data about the context of discourse in the book collection of folklore in Riau Province. The theory used in this research is the theory put forward by Hymes in Djajasudarma (2010). Methodology in this research uses content analysis method, qualitative approach and type of library research. Data collection techniques used are documentation and hermeneutic techniques. The results of this study found eight elements of discourse context, namely the background element (setting and scene) there are 142 data, participants there are 54 data, elements of results (ends) there are 13 data, message elements there are 13 data, elements of the way (key) there are 33 data, elements of facilities (instruments) there are 13 data, norms there are 13 data and type elements (genres) there are 13 data. Based on the context analysis, it can be concluded that the data in the book collection of folklore in riau province amounted to 294 data and all the context data is the most important element in building the story, because without context there will be no story.